2010
DOI: 10.1007/s10571-010-9511-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential Localization of Acid-Sensing Ion Channels 1 and 2 in Human Cutaneus Pacinian Corpuscles

Abstract: Acid-sensing ion channels (ASICs) are the members of the degenerin/epithelial sodium channel (Deg/ENaC) superfamily which mediate different sensory modalities including mechanosensation. ASICs have been detected in mechanosensory neurons as well as in peripheral mechanoreceptors. We now investigated the distribution of ASIC1, ASIC2, and ASIC3 proteins in human cutaneous Pacinian corpuscles using immunohistochemistry and laser confocal-scanner microscopy. We detected different patterns of expression of these pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 37 publications
0
35
1
1
Order By: Relevance
“…It would be also interesting for future studies to investigate mechanically activated current in dissociate DRG neurons to characterize other mechanosensory phenotypes of ASIC TKO s. We have shown slower mean conduction velocity (CV) of Aδ-AMs from ASIC TKOs. Previous studies have demonstrated the expression of ASIC2 or other channels from DEG/ENaC superfamily by human or rat Schwann cells [56], [57]. Therefore, while the exact underlying mechanism remains unclear, warranting further investigation, this might suggest a possible role of ASIC s in Schwann cell function and axonal conduction in sub-populations of afferents.…”
Section: Discussionmentioning
confidence: 97%
“…It would be also interesting for future studies to investigate mechanically activated current in dissociate DRG neurons to characterize other mechanosensory phenotypes of ASIC TKO s. We have shown slower mean conduction velocity (CV) of Aδ-AMs from ASIC TKOs. Previous studies have demonstrated the expression of ASIC2 or other channels from DEG/ENaC superfamily by human or rat Schwann cells [56], [57]. Therefore, while the exact underlying mechanism remains unclear, warranting further investigation, this might suggest a possible role of ASIC s in Schwann cell function and axonal conduction in sub-populations of afferents.…”
Section: Discussionmentioning
confidence: 97%
“…2F). Likewise, the ASIC-1, MEC-10, and MEC-6 proteins have clear orthologs in insects and in higher animals, including humans (SNN1G, PON1, and ACCN2), that form a mechanosensitive complex in branched subcutaneous sensory neurons (although PON1 may be secreted) (14,(32)(33)(34). Thus, our findings suggest the possibly of a conserved humidity-sensing strategy in which humidity levels may be encoded by the extent to which the dendritic field is stretched by skin hydration.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ASIC1a and ASIC3 are the most sensitive to H + channel proteins of these subunits than other ASIC members, which are activated by pH levels below 7.0 [33]. In contrast to ASIC1a homomers, ASIC2a shows low sensitivity to reduced extracellular pH (pH50=4.35) and slow channel inactivation [34,35]. Moreover, homomeric ASIC2a displays slower kinetics of desensitization than ASIC1a homomers [36,37].…”
Section: Structure and Characteristics Of Asicsmentioning
confidence: 99%